2022
DOI: 10.1037/xge0001094
|View full text |Cite
|
Sign up to set email alerts
|

The role of theory of mind, group membership, and apology in intergroup forgiveness among children and adolescents.

Abstract: Research on forgiveness with children and adolescents is growing, yet little is known about the developmental mechanisms that underlie intergroup forgiveness in children and adolescents. In this study, youth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…Further, research suggests that individuals' mental-state reasoning abilities may be more accurate when evaluating in-group members than out-group members (Gönültaş et al, 2020). It may be that children and adolescents have more difficulty imagining the mental state of outgroup members than in-group members (Mulvey et al, 2021). Gönültaş et al (2020) examined Turkish children's (M age = 11.66 years) mindreading and general reasoning about in-group members (Turks), similar out-group members (Syrians within Turkey), and dissimilar outgroup members (Northern Europeans).…”
Section: Differences In Tom Processing Between In-group and Out-groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, research suggests that individuals' mental-state reasoning abilities may be more accurate when evaluating in-group members than out-group members (Gönültaş et al, 2020). It may be that children and adolescents have more difficulty imagining the mental state of outgroup members than in-group members (Mulvey et al, 2021). Gönültaş et al (2020) examined Turkish children's (M age = 11.66 years) mindreading and general reasoning about in-group members (Turks), similar out-group members (Syrians within Turkey), and dissimilar outgroup members (Northern Europeans).…”
Section: Differences In Tom Processing Between In-group and Out-groupmentioning
confidence: 99%
“…However, whether ToM processing is universal across cultures (Carruthers, 2013) or influenced by individuals' cultural experiences (Kobayashi et al, 2006;Navarro & Conway, 2021;Shahaeian et al, 2014) or whether cultural universality and specificity affect children's ToM development is unclear (Hou et al, 2019). Group identify is also an important factor influencing an individual's ToM processing (Mulvey et al, 2021). It was found that children who were evaluating the mental states of an in-group member were more accurate than children evaluating the mental states of an out-group member.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dispositional forgiveness largely determines the quality of adolescents' relationships with all significant others (parents, friends, teachers, etc.). However, despite the importance of dispositional forgiveness in adolescence, relevant research in non-adult samples is not so extensive (Denham et al, 2005;Lawler-Row, 2010;Mulvey et al, 2021) maybe because the focus has been on vulnerable adolescents such as at-risk, victimized, or abused adolescents (Freedman, 2018;Liu et al, 2013). Hence, it is important to further understand dispositional forgiveness in adolescence by examining not only personality but also family and school dimensions as the two most influential domains in adolescents' lives.…”
Section: Rationale Of the Studymentioning
confidence: 99%